The effectiveness of inter‐professional working for older people living in the community: a systematic review. (14th August 2012) - Trivedi, Daksha; Goodman, Claire; Gage, Heather; Baron, Natasha; Scheibl, Fiona; Iliffe, Steve; Manthorpe, Jill; Bunn, Frances; Drennan, Vari
Abstract Health and social care policy in the UK advocates inter‐professional working (IPW) to support older people with complex and multiple needs. Whilst there is a growing understanding of what supports IPW, there is a lack of evidence linking IPW to explicit outcomes for older people living in the community. This review aimed to identify the models of IPW that provide the strongest evidence base for practice with community dwelling older people. We searched electronic databases from 1 January 1990–31 March 2008. In December 2010 we updated the findings from relevant systematic reviews identified since 2008. We selected papers describing interventions that involved IPW for community dwelling older people and randomised controlled trials (RCT) reporting user‐relevant outcomes. Included studies were classified by IPW models (Case Management, Collaboration and Integrated Team) and assessed for risk of bias. We conducted a narrative synthesis of the evidence according to the type of care (interventions delivering acute, chronic, palliative and preventive care) identified within each model of IPW. We retrieved 3211 records and included 37 RCTs which were mapped onto the IPW models: Overall, there is weak evidence of effectiveness and cost‐effectiveness for IPW, although well‐integrated and shared care models improved processes of care and have the potential to reduce hospital or nursing/care home use. Study quality varied considerably and high quality evaluations as well as observational studies are needed to identify the key components of effective IPW in relation to user‐defined outcomes. Differences in local contexts raise questions about the applicability of the findings and their implications for practice. We need more information on the outcomes of the process of IPW and evaluations of the effectiveness of different configurations of health and social care professionals for the care of community dwelling older people.